Kajian Sistem Agribisnis Jeruk Manis (Citrus Sinensis) dalam Rangka Peningkatan Pendapatan Petani di Desa Konda Satu Kecamatan Konda Kabupaten Konawe Selatan - Oni, Wa; Bahari, Bahari; Rosmawaty, Rosmawaty (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2019)
This research is based on the low income of the community, cultivation techniques and the process of harvesting sweet oranges which have not maximally causend the quality of the products produced to be difficult to compete. The aim of the study was to find out the description of the sweet orange agribusiness system and to know the size of farmers, income from sweet orange farming. This research was conducted from January to April 2019. The population was all farmers who carried out 147 orange sweet farming activities. Determination of sample was done by simple random sampling, namely by taking 25% of the population, 37 respondents. The method used to analyze the data is qualitative descriptive analysis method and income analysis. The results of the research show that the description of the sweet orange agribusiness subsystem which includes the supply and procurement of production facilities or Soprotan subsystems, the farming subsystem and the agricultural product marketing subsystem is still partial. While farmers’ income from sweet orange farming is Rp. 162.365.061/harves season whit an averagea income per farmer of Rp. 4.488.245,56/harves season and an average hectare is Rp. 5.071.355,23/harvest season with an average income per sale price of Rp. 6.279,2/kg.